Agronomic bio-fortification of wheat (Triticum aestivum L.) through iron and zinc enriched organics - Yadav, R S; Patel, A M; Dodia, I N; Aglodiya, A V; Patel, G A; Augustine, N (Journal of Cereal Research, 2011)
The short-term agricultural tools like agronomic bio-fortification of available nutrient resources as a complementary approach was initiated by applying iron and zinc as such as well as enriched with organics (FYM & Vermicompost) with two levels of recommended dose of nitrogen and phosphorus (RDNP). The RDNP with organics without iron and zinc (i.e. T1) was treated as control. The soil under study was sandy loam having low organic carbon and medium in fertility with neutral soil reaction. A significant impact of iron & zinc enriched organics were found on soil properties as well as wheat quality and production. However, both the organic sources were found at par towards all the parameters under study. The application effect of Fe-Zn enriched organics with RDNP were increased both grain as well as biomass yield of the wheat by 2.3 to 6.6% as compared to direct and by 5.6 to 10.3% as compared to no application of the micronutrients. Similarly, an appreciable improvement in SOC (28%), available nitrogen (5%) and available phosphorus (22%) was observed which are equivalent or better than control. Although, the application effect of Fe-Zn enriched organics with RDNP didn’t show any effect on nitrogen and phosphorus uptake by wheat. Therefore, these differences seem to be due to application of organics and RDNP. In contrary, the availability of Fe (5.9 to 18.4 %) & Zn (24.3 to 48.5 %) as well as their uptake (12.9 to 24.1 % for Fe and 13.4 to 28.8 % for Zn) by wheat were appreciably increased by application of Fe-Zn enriched organic as compared to direct and no application of these micronutrients. Further, it is interesting that availability (10 to 37%) as well as uptake (17 to 32%) of these micronutrients was considerably higher under 50% RDNP as compared to 100% RDNP possibly due to antagonistic effect of phosphorus. Hence, this approach would be able to conquer the micronutrient deficiency in the food and human.